# Difference between revisions of "Lucas' Theorem"

Mathgeek2006 (talk | contribs) m (→Proof) |
Mathgeek2006 (talk | contribs) m (→Proof) |
||

Line 17: | Line 17: | ||

== Proof == | == Proof == | ||

Consider <math>(1+x)^n</math>. If <math>(\overline{n_mn_{m-1}\cdots n_0})_p</math> is the base <math>p</math> representation of <math>n</math>, then <math>0\leq n_k \leq p-1</math> for all <math>0\leq k \leq m</math> and <math>n=n_mp^m+n_{m-1}p^{m-1}+\cdots+n_1p+n_0</math>. We then have | Consider <math>(1+x)^n</math>. If <math>(\overline{n_mn_{m-1}\cdots n_0})_p</math> is the base <math>p</math> representation of <math>n</math>, then <math>0\leq n_k \leq p-1</math> for all <math>0\leq k \leq m</math> and <math>n=n_mp^m+n_{m-1}p^{m-1}+\cdots+n_1p+n_0</math>. We then have | ||

− | < | + | <cmath>\begin{eqnarray*}(1+x)^n&=&(1+x)^{n_mp^m+n_{m-1}p^{m-1}+\cdots+n_1p+n_0}\\ |

&=&[(1+x)^{p^m}]^{n_m}[(1+x)^{p^{m-1}}]^{n_{m-1}}\cdots[(1+x)^p]^{n_1}(1+x)^{n_0}\\ | &=&[(1+x)^{p^m}]^{n_m}[(1+x)^{p^{m-1}}]^{n_{m-1}}\cdots[(1+x)^p]^{n_1}(1+x)^{n_0}\\ | ||

&\equiv&(1+x^{p^m})^{n_m}(1+x^{p^{m-1}})^{n_{m-1}}\cdots(1+x^p)^{n_1}(1+x)^{n_0}\pmod{p} | &\equiv&(1+x^{p^m})^{n_m}(1+x^{p^{m-1}})^{n_{m-1}}\cdots(1+x^p)^{n_1}(1+x)^{n_0}\pmod{p} | ||

− | \end{eqnarray*}</ | + | \end{eqnarray*}</cmath> |

We want the coefficient of <math>x^i</math> in <math>(1+x)^n</math>. Since <math>i=i_mp^m+i_{m-1}p^{m-1}+\cdots+i_1p+i_0</math>, we want the coefficient of <math>(x^{p^{m}})^{i_{m}}(x^{p^{m-1}})^{i_{m-1}}\cdots (x^p)^{i_1}x^{i_0}</math>. | We want the coefficient of <math>x^i</math> in <math>(1+x)^n</math>. Since <math>i=i_mp^m+i_{m-1}p^{m-1}+\cdots+i_1p+i_0</math>, we want the coefficient of <math>(x^{p^{m}})^{i_{m}}(x^{p^{m-1}})^{i_{m-1}}\cdots (x^p)^{i_1}x^{i_0}</math>. | ||

## Revision as of 19:11, 10 March 2015

**Lucas' Theorem** states that for any prime and any positive integers , if is the representation of in base and is the representation of in base (possibly with some leading s) then .

## Contents

## Lemma

For prime and ,

### Proof

For all , . Then we have Assume we have . Then

## Proof

Consider . If is the base representation of , then for all and . We then have We want the coefficient of in . Since , we want the coefficient of .

The coefficient of each comes from the binomial expansion of , which is . Therefore we take the product of all such , and thus we have

Note that .

This is equivalent to saying that there is no term in the expansion of .